Analysis Of Leading Economic Sectors In Tuban Regency And Bojonegoro Regency In East Java Using The Location Quotient, Shift Share And Klassen Typology Methods - Dyta Rizky Tamara; Marseto Marseto (International Journal of Economics, Business and Innovation Research, 2024)
The aim of this study was to determine the leading and non-leading sectors in the Tuban and Bojonegoro regencies. Although these regions are close to each other and situated on the border of Central and East Java provinces, Tuban and Bojonegoro regencies derive their local income from different sources. The research was based on time series data from the Central Statistics Agency's website in 2022. The data was analyzed using Location Quotient, Shift Share, and Klassen Typology methods. The results showed that Bojonegoro Regency has three leading sectors, while Tuban Regency has six